Virtual Reality Public Speaking Training: Experimental Evaluation of Direct Feedback Technology Acceptance - Palmas, Fabrizio; Reinelt, Ramona; Cichor, Jakub E.; Plecher, David A.; Klinker, Gudrun (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2021)
Virtual Reality (VR) offers significant potential for public speaking training. Virtual Reality Speech Training (VR-ST) helps trainees develop presentation skills and practice their application in the real world. Additionally, participants with public speaking anxiety can improve their presentation skills in a safe virtual environment without fear of judgment. Another benefit is direct feedback based on gamification principles, which provides users with information about their performance during training and allows for the adjustment of behavior in real-time. However, it is not yet clear if direct feedback based on visualization through icons is accepted by participants, such that it may support learning transfer in VR training applications. As a result, we set out to investigate how direct feedback in a VR -ST affects the participants' technology acceptance based on the Technology Acceptance Model (TAM). We conducted a between-subjects experimental study in order to compare a VR-ST with direct feedback (n = 100) with a simulation-based VR-ST (n = 100). The resulting MANOVAs demonstrated a preference for the direct feedback version for all TAM determinations, showing that direct feedback offers benefits to trainees by improving technology acceptance, independent of location and without supervision by trainers. Further results show that VR-ST is generally more accepted by participants without public speaking anxiety. Our findings indicate that developers of VR public speaking applications should focus on the inclusion of meaningful direct feedback and consider individual differences between users in order to optimally implement training measures.